ГЛАГОЛ: ДЕЙСТВИЕ И СОСТОЯНИЕ В ЯЗЫКЕ (Лучшие интеллектуальные исследования, 2025)
Аннотация.   Данная статья посвящена глаголу – одной из наиболее значимых  частей речи в языке. В ней рассматриваются основные функции глагола в предложении, такие как выражение действия, состояние , а также его роль в образовании сказуемого.Abstract:   This paper explores the verbs as a dynamic and multifaceted part of speech. As an expression of action, process, or state, the verb plays a crucial role in shaping the meaning of an utterance. The study investigates the semantic, syntactic, and morphological properties of verbs across different languages, examining how they contribute to the overall structure and interpretation of sentences.